MCSE. TCP/IP for NT Server 4 study guide - Lammle, Todd.; Lammle, Monica; Chellis, James (New Delhi : BPB, 1998)
Book includes authoritative coverage of exam topics. First CD includes an exam-preparation program, and the second CD includes live expert MCSE video instruction with hands-on exercises.
Includes index.
Keywords: Electronic data processing personnel -- Certification; Microsoft software -- Examinations -- Study guides; TCP/IP (Computer network protocol)